Peter Quennell: Shakespeare - the poet and his back-ground, Weidenfeld and Nicholson, 20 New bond street, London W. 1. First published october 1963. Reprinted with some amendments, december 1963. 325 págs., 29 ilustraciones - Pérez, Alberto (Anales de la Universidad de Chile, 1964)
-